ANALISIS PERCEIVED USEFULNESS, PERCEIVED RISK DAN TRUST TERHADAP PEMANFAATAN ATM BAGI NASABAH (Studi Pada Bank BNI di Semarang) - Nawawi, Johan (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
This study takes an object at Bank BNI in the city of Semarang, where the phenomena that occur in the use of ATM is the safety factor in any ATM, where the frequent occurrence of the crime committed by the various motives of the criminals in various ways, namely: burglary custo mer’s account even ATM machines that often occur in various ATM BNI Semarang. The purpose of this study is to analyze the influence of usability (Perceived usefulness), risk (perceived risk) and confidence (trust) to the use of customers in using ATM (usage).The sample is part of the population. The technique of determining the sample used in this study is purposive sampling, that is selecting a sample based on specific criteria. Criteria samples taken in the study were: BNI bank customers in the city of Semarang who frequently use the ATM at least once a month and want to participate in filling out questionnaires. Established research sample of 150 respondents. Data analysis methods used in this study are: t test, F test, the coefficient of determination.The results showed that the partial (individual) there is a positive and significant effect between Perceived usefulness of the utilization of the ATM BNI by the C ustomer; partial (individual) there is a negative and significant effect between Perceived Risk of Use of ATM BNI by the C ustomer; partial (individual) there is a positive and significant influence of the Trust against the use of ATM BNI by the C ustomer.